COMPARISON OF VOID FRACTION CORRELATIONS FOR DRIFT-FLUX MODEL IN VERTICAL UPWARD FLOW - Barbosa, Mariana R.; Mazza, Ricardo A.; Lima, Luiz E. M. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Multiphase flow is a common phenomenon that occurs in a variety of industries, such as petrochemical, refrigeration and chemical. The gas-liquid flows have a spatial and temporal phase distributions in a pipe section, which are related to the phases velocities, thermophysical properties and pipe geometry. Bhagwat and Ghajar (2014) developed a flow pattern independent void fraction correlation using a wide range of literature database in order to estimate the parameters of the drift-flux model, i.e., distribution parameter and local drift velocity. The main objective of this study is to compare the results of total pressure drop applying their set equation with the results using the classical parameters of drift-flux model dependent flow pattern simulated by Lima (2011) and experimental data collected by this author, Bueno (2010), Rosa and Mastelari (2008) and Owen (1986). A steady, onedimensional and isothermal air-water flow through pipes with 0.026m and 0.032m internal diameters were assumed. The frictional pressure drop was estimated using the homogenous approach. The expected result with this analysis is to verify the possibility of despising the use of flow pattern maps in the description of the air-water hydrodynamic behavior.